Assessing Religious Literacy in Indonesian Secondary Education and Its Implications for Religious Moderation - Noer Hidayah; Akhiarul Waro Wardani; Wahidul Anam; Mona Addeq (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
Religious moderation is a national priority for preventing conflicts rooted in religious differences, yet empirical studies that map the multidimensional structure of religious literacy among Indonesian adolescents remain limited. This study addresses this gap by examining the level and profile of religious literacy among senior high school students in Kediri City. A quantitative survey design was used, drawing on structured questionnaire data from students at MAN 1 Kediri City and SMAN 4 Kediri City, and the analysis employed descriptive statistics and profile analysis to differentiate between normative and critical‑interpretive competencies. The results show that 86.3 percent of students demonstrate high to very high religious literacy, particularly in respecting religious diversity, supporting religious freedom, and applying ethical values in daily life. Lower performance appears in higher-order competencies such as recognizing religion-based violence, interpreting sacred texts within socio-political contexts, and engaging in interfaith dialogue, indicating that students possess strong normative understanding but weaker analytical and dialogical skills. These findings suggest that current educational practices effectively cultivate basic attitudes of tolerance but do not sufficiently strengthen competencies needed to navigate complex religious issues in plural societies. The study concludes that targeted interventions are required to enhance critical‑interpretive dimensions of religious literacy and recommends integrating structured interfaith dialogue activities, contextual text interpretation exercises, and critical reflection modules to support national religious moderation agendas in secondary education.   ABSTRAK Penguatan sikap moderasi beragama merupakan salah satu upaya strategis pemerintah untuk memitigasi konflik yang timbul akibat perbedaan keagamaan. Literasi beragama berperan sebagai kompetensi dasar dalam menumbuhkan moderasi tersebut. Penelitian ini mengkaji tingkat dan profil literasi beragama siswa sekolah menengah atas di Kota Kediri dengan menggunakan pendekatan survei kuantitatif yang melibatkan siswa MAN 1 Kota Kediri dan SMAN 4 Kota Kediri. Hasil penelitian menunjukkan bahwa 86,3% siswa memiliki tingkat literasi beragama tinggi hingga sangat tinggi, khususnya dalam aspek penghormatan terhadap keberagaman agama, penegakan kebebasan beragama, serta penerapan nilai-nilai etika dalam kehidupan sehari-hari. Namun demikian, masih terdapat kelemahan yang signifikan pada kompetensi tingkat lanjut, seperti kemampuan mengidentifikasi kekerasan berbasis agama, menafsirkan teks keagamaan dalam konteks sosial-politik, keterampilan berdialog lintas agama, serta kemampuan mengevaluasi secara kritis gerakan keagamaan dari perspektif kemanusiaan. Penelitian ini menyajikan kebaruan empiris dengan memetakan literasi beragama tidak hanya sebagai sikap umum, tetapi sebagai konstruk multidimensi yang membedakan antara pemahaman normatif dan kompetensi kritis-interpretatif pada remaja. Temuan ini berkontribusi secara teoretis terhadap konseptualisasi literasi beragama sebagai fondasi moderasi beragama yang terukur serta memberikan implikasi kebijakan bagi perancangan intervensi pendidikan yang terarah untuk memperkuat agenda moderasi beragama di jenjang menengah.Bottom of Form